Mutation-induced alterations of intra-filament subunit organization in vimentin filaments revealed by SAXS - Brennich, Martha E.; Vainio, Ulla; Wedig, Tatjana; Bauch, Susanne; Herrmann, Harald; Koester, Sarah (Soft Matter, 2019)
Vimentin intermediate filaments constitute a distinct filament system in mesenchymal cells that is instrumental for cellular mechanics and migration. In vitro, the rod-like monomers assemble in a multistep, salt-dependent manner into micrometer long biopolymers. To disclose the underlying mechanisms further, we employed small angle X-ray scattering on two recombinant vimentin variants, whose assembly departs at strategic points from the normal assembly route: (i) vimentin with a tyrosine to leucine change at position 117; (ii) vimentin missing the non-a-helical carboxyl-terminal domain. Y117L vimentin assembles into unit-length filaments (ULFs) only, whereas DT vimentin assembles into filaments containing a higher number of tetramers per cross section than normal vimentin filaments. We show that the shape and inner structure of these mutant filaments is significantly altered. ULFs assembled from Y117L vimentin contain more, less tightly bundled vimentin tetramers, and DT vimentin filaments preserve the number density despite the higher number of tetramers per filament cross-section.
CRIS-Team WoS Importer:2019-03-15